Zika Virus Vector Competency of Mosquitoes, Gulf Coast, United States - Charles E. Hart (Emerging Infectious Diseases, 2017)
Zika virus has recently spread throughout the Americas. Although Aedes aegypti mosquitoes are considered the primary vector, Culex quinquefasciatus and mosquitoes of other species may also be vectors. We tested Cx. quinquefasciatus and Ae. taeniorhynchus mosquitoes from the US Gulf Coast; both were refractory to infection and incapable of transmission.